2012
DOI: 10.1186/1479-5876-10-253
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbial determinants of fecal and systemic estrogens and estrogen metabolites: a cross-sectional study

Abstract: BackgroundHigh systemic estrogen levels contribute to breast cancer risk for postmenopausal women, whereas low levels contribute to osteoporosis risk. Except for obesity, determinants of non-ovarian systemic estrogen levels are undefined. We sought to identify members and functions of the intestinal microbial community associated with estrogen levels via enterohepatic recirculation.MethodsFifty-one epidemiologists at the National Institutes of Health, including 25 men, 7 postmenopausal women, and 19 premenopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
410
5
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 462 publications
(426 citation statements)
references
References 37 publications
8
410
5
3
Order By: Relevance
“…However, whether the increasing of steroid hormones throughout the pregnancy account to the change of the fecal bacteria composition in Meishan sows need to be elucidate in the future. However, present sequencing profile did not find obvious difference in the richness estimators (ACE and Chao), and the diversity indices (Shannon and Simpson) of fecal bacterial community between the different gestation time in Meishan pigs, this did not agree with the studies in men and postmenopausal women, in which, the urinary estrogens concentration were changed strongly and directly associated with all measures of fecal microbiome diversity and composition [23]. Numbers of studies have proved that, the dietary composition can modify the gut microbial profiles [24].…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…However, whether the increasing of steroid hormones throughout the pregnancy account to the change of the fecal bacteria composition in Meishan sows need to be elucidate in the future. However, present sequencing profile did not find obvious difference in the richness estimators (ACE and Chao), and the diversity indices (Shannon and Simpson) of fecal bacterial community between the different gestation time in Meishan pigs, this did not agree with the studies in men and postmenopausal women, in which, the urinary estrogens concentration were changed strongly and directly associated with all measures of fecal microbiome diversity and composition [23]. Numbers of studies have proved that, the dietary composition can modify the gut microbial profiles [24].…”
Section: Discussioncontrasting
confidence: 48%
“…Numbers of studies have proved that, the dietary composition can modify the gut microbial profiles [24]. Flores et al [23] had excluded the dietary patterns effect by dietary restrictions (vegan or vegetarian, gluten, lactose, peanuts, pork or shellfish) [23], but it is difficult to make all volunteers refine their diet on one recipe throughout the investigation. Whereas, the research on pigs has the advantage of fixing feed composition through the experimental period.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, decreased diversity is regarded as an indicator of disease state, reflecting a deteriorating habitat and/or depleted resources (91). Interestingly, estrogen depletion has also been associated with decreased α-diversity in the gut microbiome (92,93), while microbial diversity in the gut transiently increases with administration of probiotics (94). Therefore, we hypothesize that sex steroid deficiency leads to decreased microbiota diversity and that LGG and VSL#3 probiotics restore a greater diversity.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, we and others have hypothesized that systemic levels of EMs may be modulated, in part, by the metabolic and other activities of gut microbiota (13,14). In a previous study that included 25 men and seven postmenopausal women, we observed that measures of fecal microbiome richness and ␣-diversity were directly associated with levels of urinary EMs and inversely associated with levels of fecal EMs (15). Here we present a study of the fecal microbiome in association with urinary EM profiles in a sample of 60 postmenopausal women.…”
mentioning
confidence: 79%
“…Fecal DNA isolation, 454 Pyrosequencing of barcoded 16S rRNA genes, and filtering of reads through the Institute of Genome Sciences bioinformatics pipeline were performed as described previously by Flores et al (15). Four samples had extremely low numbers of reads, suggesting a problem with amplification steps; the extraction and amplification were repeated, but two samples were ultimately excluded from the analysis.…”
Section: Fecal Sample Processing and Analysismentioning
confidence: 99%